The Technique of Optimal Use of Facial Muscles in Trumpet Interpretation - Horez Iulian (Sciendo, 2019)
Facial muscles have an overwhelming importance in obtaining a special sonority, a perfect instrumental technique. In fact, through their vibration all sonority is produced by these muscles, and the level of professionalism one can reach depends on their degree of efficient use. We shall next analyze the specific issues and modality of use. While playing a mouthpiece instrument, due to the way facial muscle s are used, the following issues arise: exaggerated facial muscles stretching, clamping, undue strain, vibration limitation (by over-pressing, outer reason).